2009
DOI: 10.1091/mbc.e08-10-0989
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Mechanism to Achieve Efficient Signal Recognition Particle (SRP)–SRP Receptor Interaction by the Chloroplast SRP Pathway

Abstract: Cotranslational protein targeting by the signal recognition particle (SRP) requires the SRP RNA, which accelerates the interaction between the SRP and SRP receptor 200-fold. This otherwise universally conserved SRP RNA is missing in the chloroplast SRP (cpSRP) pathway. Instead, the cpSRP and cpSRP receptor (cpFtsY) by themselves can interact 200-fold faster than their bacterial homologues. Here, cross-complementation analyses revealed the molecular origin underlying their efficient interaction. We found that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
(89 reference statements)
2
26
0
Order By: Relevance
“…As shown in previous work and in the preceding paper (51), the M-domain of cpSRP54 interacts with conserved basic residues in the cpFtsY G-domain; this interaction is required for rapid assembly of a stable cpSRP54⅐cpFtsY complex that was previously observed only when an artificial stimulant, Nikkol, was used (28). Intriguingly, here we found that both the liposome-induced stimulation of the cpSRP54⅐cpFtsY complex assembly and the Alb3-mediated regulation of GTP hydrolysis in this complex also require the M-domain of cpSRP54.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As shown in previous work and in the preceding paper (51), the M-domain of cpSRP54 interacts with conserved basic residues in the cpFtsY G-domain; this interaction is required for rapid assembly of a stable cpSRP54⅐cpFtsY complex that was previously observed only when an artificial stimulant, Nikkol, was used (28). Intriguingly, here we found that both the liposome-induced stimulation of the cpSRP54⅐cpFtsY complex assembly and the Alb3-mediated regulation of GTP hydrolysis in this complex also require the M-domain of cpSRP54.…”
Section: Discussionsupporting
confidence: 63%
“…As described in the accompanying paper (51), the cpSRP54 M-domain provides a platform to coordinate rapid and stable complex assembly between cpSRP54 and cpFtsY, thus replacing the otherwise conserved SRP RNA (28). Interestingly, deletion of the cpSRP54 M-domain abolished the stimulatory effect of PG on complex assembly (Fig.…”
Section: Anionic Phospholipids Stimulate Cpsrp54⅐cpftsy Complexmentioning
confidence: 66%
See 1 more Smart Citation
“…The finding that the preformed closed conformation of cpFtsY is not phylogenetically correlated to the loss of the cpSRP RNA indicates that this conformational change of cpFtsY is not sufficient to enable an efficient cpFtsY/cpSRP54 complex formation. Interestingly, it has been shown that in Arabidopsis the M-domain of cpSRP54 mimics the function of the SRP RNA by providing a significant acceleration of complex formation between the cpSRP GTPases (Jaru- Ampornpan et al, 2009). This leads to the speculation that the M-domain of P. patens cpSRP54 might still resemble the classic bacterial M-domain, which has no stimulating influence on complex formation (Jaru-Ampornpan et al, 2009) and might therefore still depend on an SRP RNA for efficient cpFtsY binding.…”
Section: Phylogenetic Distribution Structure and Function Of Plastimentioning
confidence: 99%
“…It was suggested that this modified position of the Asp residue in cpFtsY contributes to the significantly higher nucleotide specificity compared with prokaryotic FtsY (Jaru-Ampornpan et al, 2007;Chandrasekar et al, 2008). Besides the closed conformation of cpFtsY, the M-domain of cpSRP54 was shown to play an important role for an efficient interaction between the cpSRP GTPases by stimulating complex formation (Jaru-Ampornpan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%